Hyperparathyroidism after renal transplantation. - Kleerekoper, M (1975)
Renal transplantation reduced circulating parathyroid hormone in recipients of renal allografts. Nevertheless, biochemical and histological evidence of mild hyperparathyroidism persisted up to eight years after renal transplantation despite good graft function.